Organ donation in the lab: Preferences and votes on the priority rule - Annika Herr; Hans-Theo Normann (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
An allocation rule that prioritizes registered donors increases the willingness to register for organ donation, as laboratory experiments show. In public opinion, however, this priority rule faces repugnance. We explore the discrepancy by implementing a vote on the rule in a donation experiment, and we also elicit opinion poll-like views. We find that two-thirds of the participants voted for the priority rule in the experiment. When asked about real-world implementation, participants of the donation experiment were more likely to support the rule than non-participants. We further confirm previous research in that the priority rule increases donation rates. Beyond that, we find that medical school students donate more often than participants from other fields.
Keywords: C90; I10; I18; 330; organ donation; laboratory experiment; vote